واقع ترشيد استهلاك الطاقة في المنشآت الصناعية من اجل تحقيق أهداف التنمية المستدامة –حالة مؤسسة الاسمنت ومشتقاته بالشلف - سراج, وهيبة; بوذريع, صاليحة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى التأكيد على حاجة المنشآت الصناعية لرفع كفاءة استخدامها للطاقة، وابراز الآثار التي أفرزتها عملية الترشيد على الصعيد الاقتصادي والاجتماعي والبيئي، وتداعيات هذه الآثار على فرص تحقيق التنمية المستدامة. توصلت الدراسة إلى أن تحسين كفاءة استخدام الطاقة في المنشآت الصناعية يساهم في حماية الموارد الطاقوية، كما يخفض تكلفة الإنتاج وزيادة قدرتها على المنافسة، بالإضافة الى المردود الايجابي على البيئة من منظور الاستخدام الأكفأ للطاقة. This study aims to emphasize the need for industrial facilities to raise the efficiency of their use of energy, and highlight the effects of the rationalization process on the economic, social and environmental levels, and repercussions these effects opportunities for sustainable development. The study concluded that improving the efficiency of energy use in industrial facilities contributes to the protection of energy resources, as well as reducing the cost of production and increasing its competitiveness, In addition to the positive impact on the environment from the perspective of the most efficient use of energy.
مقال
Keywords: طاقة ; صيانة ; تنمية مستدامة ; منشات صناعية